Prediction of hydrogen production of a downdraft gasifier using equilibrium modeling for different moisture content for solid oxide fuel cell action (sofc). - Boloy, Ronney Arismel Mancebo; Silveira, Jose Luz; Silva, Marcio Evaristo (Revista Ciências Exatas, 2009)
Equilibrium modeling has been used to predict the hydrogen production in a downdraftgasifier. The composition of syngas (synthesis gas), the lower heat value (LHV), hence, the coldefficiency of gasifier (?cg) have been determined. The effects of moisture content (MC) have beeninvestigated for temperature of gasification 800 °C. The predicted values compare reasonably wellwith experimental data available in literature. The amount of hydrogen and CH4 increase withincrease in the range of moisture content in the biomass (eucalyptus) investigated. The LHV andcold efficiency of gasifier decreases with increase in the range of moisture content.